Sleep and cognitive function in chronic stroke: a comparative cross-sectional study. Issue 5 (26th February 2019) - Falck, Ryan S; Best, John R; Davis, Jennifer C; Eng, Janice J; Middleton, Laura E; Hall, Peter A; Liu-Ambrose, Teresa
Abstract: Poor sleep is common following stroke, limits stroke recovery, and can contribute to further cognitive decline post-stroke. However, it is unclear what aspects of sleep are different in older adults with stroke compared with those without, and whether the relationship between sleep and cognitive function differs by stroke history. We investigated whether older adults with stroke experience poorer sleep quality than older adults without stroke, and whether poor sleep quality attenuates cognitive performance among older adults with a history of stroke. Thirty-five age- and sex-matched older adults with stroke (age: 69.86 ± 1.13 years; 51.43% female) and without stroke (age: 69.83 ± 1.12; 51.43% female) were compared with respect to sleep quality using the MotionWatch8 (MW8) and Pittsburgh Sleep Quality Index (PSQI). Cognitive performance was indexed using the Alzheimer's Disease Assessment Scale Plus (ADAS-Cog Plus). Additionally, we examined whether poor sleep quality is associated with poorer cognitive performance among older adults with stroke. Older adults with stroke had longer MW8 measured sleep duration (27.82 ± 12.17 min; p = 0.03) and greater fragmentation (6.44 ± 2.24; p < 0.01), but did not differ in PSQI from their nonstroke peers. There was a significant group x sleep quality interaction for fragmentation (β = 0.02; p < 0.01) and efficiency (β = −0.03; p = 0.02) on ADAS-Cog Plus performance, whereby differences in cognitive performance between older adults with and without stroke were accentuated in the presence of poor sleep quality. Older adults with stroke have poorer sleep quality than their nonstroke counterparts, and older adults with stroke and poor sleep quality experience larger deficits in cognitive performance. Clinical Trial Registration : Vitality: Promoting Cognitive Function in Older Adults With Chronic Stroke (Vitality); https://clinicaltrials.gov/ct2/show/NCT01916486 ; NCT01916486